Ověření normálního rozdělení - méně běžné testy - Kubanová, Jana (Univerzita Pardubice, 2002)
The normal distribution of population is presumtion of many statistical tests. The acceptance of this presumption is most frequently tested by chi-square test and by one-sample Kolmogorov-Smirnov's test. Some other tests are described in this article, serving for confirmation of this hypothesis, such as the tests based on skewness and curtosess, the Jarque - Berra's test, the Shapiro-Wilk's normality test and the D'Agostin test.
Keywords: matematika; statistika; testy; statistické testy